Post-translational modifications of PML: consequences and implications - Cheng, Xiwen; Kao, Hung-Ying (Frontiers in Oncology, 2013)
The tumor suppressor promyelocytic leukemia protein (PML) predominantly resides in a structurally distinct sub-nuclear domain called PML nuclear bodies (NBs). Emerging evidences indicated that PML actively participates in many aspects of cellular processes, but the molecular mechanisms underlying PML regulation in response to stress and environmental cues are not complete. Post-translational modifications, such as sumoylation, phosphorylation, acetylation, and ubiquitination of PML add a complex layer of regulation to the physiological function of PML. In this review, we discuss the fast-moving horizon of post-translational modifications targeting PML.